Using ultrafine particles from a coal washing plant in metallurgical coke production (2011)
Blending ultrafine particles from a coal washing plant was studied for coke production by briquetting using 6%w coal tar as binder. The ultrafine coal particles were characterised and a pilot coking test was made in a Koppers’ furnace. Coke quality was evaluated by proximate analysis, stability (micum 10 and micum 40), coke reactivity index (CRI) with CO2 and the coke’s mechanical strength after reaction with carbon dioxide (CSR index). Briquetting results showed that was possible to obtain coke having 19.0 % CRI and 75.6% CSR, these being the characteristics required in metallurgical processes.